Thermal analysis of mixtures of wheat flour and potato starches - Sarker, Md. Zaidul Islam; Yamauchi, Hiroaki; Matsuura-Endo, Chie; Takigawa, Shigenobu; Noda, Takahiro (Elsevier Inc., 2008)
Potato starches with various contents of amylose from the Eniwa, Benimaru, and Norin No. 1 cultivars were blended with wheat flour at 10 to 50% potato starch (on a weight basis), and differential scanning calorimetry (DSC) studies were then conducted to determine if there were any traces of starch at 30% wt suspension. The amylose content of Eniwa potato starch was higher than those of the Benimaru and Norin No. 1 potato starches. Eniwa potato starch also exhibited significantly higher DSC traces than the Benimaru and Norin No. 1 potato starches. The DSC traces of the gelatinization peak temperature (TP) of the Eniwa potato starch–wheat flour mixture remained almost identical up to 30% and then showed a tendency to decrease from 40% potato starch in the mixtures due to significant dilution of wheat flour by potato starches at 40 and 50%. However, the TP values of the Eniwa potato starch–wheat flour mixture were significantly higher than those of the Benimaru potato starch–wheat flour and Norin No. 1 potato starch–wheat flour mixtures, and exhibited a trailing shoulder up to 40% Eniwa potato starch. On the other hand, no trailing shoulder was evident at 50% Eniwa potato starch in the mixture or in the Benimaru and Norin No. 1 potato starch–wheat flour mixtures. Such phenomena occurred due to the smaller differences in the TP of the control wheat flour, Benimaru and Norin No. 1 potato starches. The TP of the mixtures was slightly higher than that of the control samples due to the influences of the wheat gluten in the mixtures. r 2007 Elsevier Ltd. All rights reserved.